Control of anterior segment using an antero-posterior lingual sliding retraction system: a preliminary cone-beam CT study - Min Hwang; Hyo-Won Ahn; Soon-Yong Kwon; Jeong-Ho Choi; Seong-Hun Kim; Gerald Nelson (SpringerOpen, 2018)
Abstract Background This study was performed to evaluate the treatment effects of the antero-posterior lingual retractor (APLR), focusing on the 3-dimensional (3D) tooth movement of the maxillary anterior teeth and their alveolar bone levels. Methods En masse retraction was performed using either the C-lingual retractor (CLR, C-group, n = 9) or the antero-posterior lingual retractor (APLR, AP-group, n = 8). We evaluated 3D movement of the maxillary anterior teeth and alveolar bone levels, root length of the central incisors, long axes of the maxillary canines, and occlusal plane changes from CBCT images. Results After retraction, the central incisors were more significantly intruded and their root apex was more retracted in the AP-group. The long axis of the canine was well maintained in the AP-group. There were no differences in the steepness of occlusal plane and the incidence of alveolar bone loss or of root resorption during en masse retraction with the two retractors. Conclusions The clockwise bowing effect of the anterior segment was less with the APLR, which prevented unwanted canine movement.